The Influence of Sharia Accounting Knowledge, Financial Awards, and Work Environment on the Interest of Students of the Accounting Department at Mulawarman University in Career in Sharia Financial Institutions - Irwandi, Muhammad; Musviyanti (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This paper examines the influence of sharia knowledge, financial rewards and work environment on the interest of accounting students in a career in Sharia Financial Institutions. The sample for this study is students majoring in accounting, Faculty of Economics and Business, Mulawarman University. The method used is a quantitative approach. Data collection was carried out by distributing questionnaires. The analysis method uses Partial Least Square (PLS). The results of this study show that knowledge of sharia accounting and the Work Environment have a positive and significant influence on the interest of accounting students in a career in Islamic Financial Institutions while financial awards do not have a significant effect on the interest of accounting students in a career in Islamic financial institutions